Intestinal Bacteria Encapsulated by Biomaterials Enhance Immunotherapy - Liu, Yilun; Li, Zhongmin; Wu, Yuanyu; Jing, Xiabin; Li, Lin; Fang, Xuedong (Frontiers in Immunology, 2021)
The human intestine contains thousands of bacterial species essential for optimal health. Aside from their pathogenic effects, these bacteria have been associated with the efficacy of various treatments of diseases. Due to their impact on many human diseases, intestinal bacteria are receiving increasing research attention, and recent studies on intestinal bacteria and their effects on treatments has yielded valuable results. Particularly, intestinal bacteria can affect responses to numerous forms of immunotherapy, especially cancer therapy. With the development of precision medicine, understanding the factors that influence intestinal bacteria and how they can be regulated to enhance immunotherapy effects will improve the application prospects of intestinal bacteria therapy. Further, biomaterials employed for the convenient and efficient delivery intestinal bacteria to the body have also become a research hotspot. In this review, we discuss the recent findings on the regulatory role of intestinal bacteria in immunotherapy, focusing on immune cells they regulate. We also summarize biomaterials used for their delivery.